Pengaruh Suhu dan Lama Pengeringan terhadap Sifat Kimia dan Fungsional Tepung Kecambah Kacang Merah (Phaseolus Vulgaris L.) - Widiantini, Ni Luh Putu Mayra Putri; Wisaniyasa, Ni Wayan; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPA, 2024)
Red beans are a source of vegetable protein. One of the processes for handling red beans is germination. Red sprouts can be turned into flour to extend their shelf life and reduce the unpleasant odor that is usually present in legume products. The quality of flour products is greatly influenced by temperature and drying time, because inappropriate conditions can cause microbial growth and undesirable reactions. The main objective of this study was to assess how temperature and drying time affect the chemical and functional properties of red bean sprout flour. Apart from that, this research also aims to identify the optimal temperature and drying time required to produce red bean sprout flour with the desired characteristics. This research used a Randomized Block Design with a factorial pattern. The first factor investigated was the drying temperature, which was divided into three different levels: 50, 60, and 70°C. The next factor considered is drying time which is also categorized into three levels: 14 hours, 16 hours, and 18 hours. The data that was collected underwent analysis through variance. If the treatment had an impact on the observed variables, the analysis proceeded with a Duncan Multiple Range Test. The research results showed that the most effective treatment for producing red bean sprout flour was achieved with a drying temperature of 70oC and a drying time of 16 hours. This treatment produces red bean sprout flour with the following characteristics; water content 5.16% protein content 22.8%, wettability 142.385 seconds, water absorption capacity 211.35%, water solubility index 50.39%, oil absorption capacity 96.584%, and swelling power 388.20%.